Farnesol inhibits cell proliferation and induces apoptosis after partial hepatectomy in rats - Chagas,Carlos Eduardo Andrade (2009)
PURPOSE: To study farnesol (FOH) effects on liver regeneration after 70% partial hepatectomy (PH) in rats. METHODS: Animals received FOH (25 mg/100 g body weight/day) or corn oil (CO, 0.25 mL/100 g body weight/day, controls). After a 2 week-treatment, all animals were subjected to PH and euthanized at different time points (0 h, 0.5 h, 4 h, 8 h, 18 h and 24 h) after surgery. Hepatic cell proliferation (PCNA positive nuclei) and apoptosis (fluorescence microscopy) were evaluated. RESULTS: Compared to CO treatment, FOH treatment inhibited (p<0.05) cell proliferation at 24h (S phase of the cell cycle) after PH. This was preceded by an induction of apoptosis 0.5 h (p<0.05; G0/G1 transition phase) after surgery. CONCLUSION: The results of the present study suggest that apoptosis induction could be associated with the reduced number of cells at the S phase observed in FOH group. These novel in vivo data reinforce FOH as a promising chemopreventive and therapeutic agent against cancer.